Case Report: Pulmonary Conidiobolomycosis in a Vietnamese Pot-Bellied Pig - Rasche, Brittany L.; Tucker, Samuel M.; Linder, Keith; Harrison, Tara M.; Negrão Watanabe, Tatiane Terumi (Frontiers in Veterinary Science, 2021)
An adult castrated male Vietnamese pot-bellied pig had a 1-week history of acute dyspnea and lethargy. Minimal diagnostic testing was authorized by the owner, resulting in treatment with a third-generation cephalosporin and a nonsteroidal anti-inflammatory drug. Partial improvement was observed after a week; however, the pig died two weeks after the initial onset of clinical signs. Macroscopically, approximately 90% of the left lung was effaced by large masses with a caseonecrotic center. Histologic examination revealed eosinophilic granulomas with myriad, intralesional, negatively staining hyphae highlighted by “sleeves” of hypereosinophilic material (Splendore-Hoeppli material). Infection with an oomycete or “zygomycete” (i.e. organisms of the order Entomophthorales or Mucorales) was initially considered. Pan-fungal PCR and sequencing performed on formalin-fixed, paraffin-embedded lung tissue identified Conidiobolus spp., consistent with a diagnosis of primary pulmonary conidiobolomycosis. There are only a few reports of infections with Conidiobolus spp. (and other members of the order Entomophthorales) in swine. Unlike humans and other animal species, conidiobolomycosis in pigs presents more commonly as a primary pulmonary disease rather than rhinofacial or nasopharyngeal disease.